Adapting the I-PASS Handoff Program for Emergency Department Inter-Shift Handoffs - Heilman, James A. (West J Emerg Med, 2016)
INTRODUCTION: Academic emergency department (ED) handoffs are high-risk transfer of care events. Emergency medicine residents are inadequately trained to handle these vital transitions. We aimed to explore what modifications the I-PASS (illness severity, patient summary, action list, situation awareness and contingency plans, and synthesis by receiver) handoff system requires to be effectively modified for use in ED inter-shift handoffs. METHODS: This mixed-method needs assessment conducted at an academic ED explored the suitability of the I-PASS system for ED handoffs. We conducted a literature review, focus groups, and then a survey. We sought to identify the distinctive elements of ED handoffs and discern how these could be incorporated into the I-PASS system. RESULTS: Focus group participants agreed the patient summary should be adapted to include anticipated disposition of patient. Participants generally endorsed the order and content of the other elements of the I-PASS tool. The survey yielded several wording changes to reflect contextual differences. Themes from all qualitative sources converged to suggest changes for brevity and clarity. Most participants agreed that the I-PASS tool would be well suited to the ED setting. CONCLUSION: With modifications for context, brevity, and clarity, the I-PASS system may be well suited for application to the ED setting. This study provides qualitative data in support of using the I-PASS tool and concrete suggestions for how to modify the I-PASS tool for the ED. Implementation and outcome research is needed to investigate if the I-PASS tool is feasible and improves patient outcomes in the ED environment.